2015
DOI: 10.3748/wjg.v21.i17.5167
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and gender-specific disparities in colorectal cancer risk

Abstract: Colorectal cancer is one of the most common causes of cancer morbidity both in men and in women. However, females over 65 years old show higher mortality and lower 5-year survival rate of colorectal cancer compared to their age-matched male counterparts. The objective of this review is to suggest gender-based innovations to improve colorectal cancer outcomes in females. Women have a higher risk of developing right-sided (proximal) colon cancer than men, which is associated with more aggressive form of neoplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
319
6
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(361 citation statements)
references
References 56 publications
21
319
6
15
Order By: Relevance
“…Statistics from Korea and Japan have indicated that women over 65 years show a higher mortality and lower 5-year survival compared to their age-matched male counterparts [33,34]. Further, a review from 2015 covering gender impact on CRC suggests that both genetic factors, dietary habits and socio-cultural environmental factors may attribute to a gender-specific disparity [35]. A review from 2012 reports that women are more prone to right-sided colon cancer than men, associated with a poorer prognosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Statistics from Korea and Japan have indicated that women over 65 years show a higher mortality and lower 5-year survival compared to their age-matched male counterparts [33,34]. Further, a review from 2015 covering gender impact on CRC suggests that both genetic factors, dietary habits and socio-cultural environmental factors may attribute to a gender-specific disparity [35]. A review from 2012 reports that women are more prone to right-sided colon cancer than men, associated with a poorer prognosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found in previous studies that the incidence of CRC was more common in females than males, in older persons (more than 65 years) [7,8]. The average age of persons in this study was 65.…”
Section: Resultsmentioning
confidence: 68%
“…There are gender differences in CRC. The incidence of CRC is higher in females than in males, when considering persons older and 65 years [7,8]. The 5-year survival rate for colorectal cancer in females, over the age of 70, is higher than that for males [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we did survival analysis by cancer type (n=228, cancer type: colorectal adenocarcinoma, cancer type The site and subtype of cancer, and the prognosis of patients depend on gender, stage, race etc [12][13][14][15][16][17]. For these reasons, subgroup analysis is required to identify stage-and genderspecific prognostic genes.…”
Section: Survival Analysis By Mrna or Cancer Typementioning
confidence: 99%